How Is The Implementation Of IFRS 17/PSAK 117 And Its Impact On Risk Based Capital Of Life Insurance Companies? - Sisca; Zuliani Dalimunthe (Dinasti Publisher, 2024)
The implementation of IFRS 17 in 2025 will impact the reporting of insurance contracts and potentially affect the calculation of Risk Based Capital (RBC) for insurance companies. This study evaluates how IFRS 17 affects insurance contract liabilities and solvency ratios in insurance companies, using a sizeable Indonesian life insurance company as a case study. The research covers traditional products, health insurance, and unit-linked products, with findings validated through interviews with actuarial or accounting heads from five other life insurance companies. The study reveals that liabilities for traditional insurance contracts increase, unit-linked product liabilities decrease, and short-term health insurance liabilities remain unchanged. These changes will impact RBC calculations even though IFRS 17 does not alter the inherent business risks of insurance companies. The study recommends that regulators adjust RBC calculations to ensure financial statements accurately reflect insurance companies' financial health and risks.